RELEVANSI PEMIKIRAN MAHATMA GANDHI TERHADAP PEMBERANTASAN KORUPSI DI INDONESIA - Zainal Fadri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2026)
The issue of corruption that occurs in various parts of the country is a matter of concern for all people. There are many preventive activities carried out by the government and regulatory agencies, but the results have not shown a positive number for the decline. Many institutions create designs and systems to prevent acts of corruption, but corrupt behavior remains a major problem for countries in the world. even many large countries were destroyed by acts of corruption. This study aims to provide an overview of the prevention or eradication of corruption with other approaches. The approach used is more directed at the personal approach of corrupt behavior. After getting a good understanding of corruption, then a system will be created that will lead every corrupt behavior to self-realization so as not to become corrupt. The data of this study were obtained from literacy collection then compiled and analyzed in order to obtain a picture and conclusion that corruption cases can be resolved by other methods, namely using the method introduced by Mahatma Gandhi, namely the approach to meaning and the approach of the human person.